Epicurus on bivalence and the excluded middle - Bown, A (De Gruyter, 2016)
In several of his philosophical works, Cicero gives reports of the Epicurean views on bivalence and the excluded middle that are not always consistent. I attempt to establish a coherent account that fits the texts as well as possible and can reasonably be attributed to the Epicureans. I argue that they distinguish between a semantic and a syntactic version of the law of the excluded middle, and that whilst they reject bivalence and the semantic law for fear of certain fatalistic consequences, they endorse the syntactic law. Subsequently, I show that certain principles that they seem to endorse in the context of Cicero’s discussion of Chrysippus’ argument for fate, when modified by the addition of the atomic swerve, suggest that the Epicureans have in mind something like a supervaluationist model of truth at times, which has the desired results with respect to the three logical principles.